Functioning of Local Government in Bangladesh: Legal and Practical Spheres - Nishat, Abu Jakaria; Popov, Dmitry; Mukharjee, Shanjay Kumar; Victorovna, Avakova Olga; Biswas, Bikram (Advances in Social Sciences Research Journal, 2021)
Local government is a fundamental part of Government and undeniable part of development in all spheres of a country. While most of the constructions in the worlds pronounce various provisions of having local government, it’s got more significance in recent time. Moreover, without overall participation of the population of a country, development of all sectors can’t be achieved. Participation of grassroots people are encouraged and ensured by local institutions. It also provides the opportunities to the population oriented of making policies and implementing decision better for them which is ultimately a step forwarding sustainable development. Since the time of independence from Pakistan in 1971, Bangladesh has local government system in the constitution of the country. Various amendments regarding local government have been brought basically when regimes changed. Thus, till to date, the constitutional provisions have been far dream from the reality. In the very root level the local government established maintaining the constitutional provisions can extend the practice of democracy. Thus, following constitutional scheme and to enhance good governance at all levels of the society, it’s ripe time for the concerned authority to be more conscious to establish local government.